STRATEGI MEMBANGUN KEUNGGULAN SEKOLAH MELALUI PROGRAM INOVASI ECOBRICK DI SMP NEGERI 23 PEKANBARU - Zulfadli Lilmuttaqin; Iqbal Syahputra; Muthiah Arifah Tri Cikadiwa; Rahma Aulia Putri; Raudhoh Assakinah Yasti; Sintya Lestari; Padila Khoirani; Risalbiyah Aina Sabma (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze the strategies employed by SMP Negeri 23 Pekanbaru in building school excellence through the Ecobrick innovation program, identify supporting and inhibiting factors in its implementation, and examine its impact on environmental quality, student character development, and school reputation. This research used a qualitative descriptive approach. Data were collected through observations, interviews, and documentation, then analyzed systematically. The findings revealed that the development strategy of the Ecobrick program was carried out through careful planning, integration into the school curriculum, active involvement of all school members, particularly the student council (OSIS), regular implementation of Ecobrick Day activities, and collaboration with external stakeholders. The program was implemented by processing plastic waste into ecobricks, which were utilized for constructing school facilities such as literacy parks, school fences, student council rooms, and various school furniture. Supporting factors included visionary school leadership, curriculum integration, active student participation, consistent program implementation, and support from external stakeholders. Meanwhile, the inhibiting factors were limited production facilities, students’ initial lack of understanding, and suboptimal waste sorting practices. The Ecobrick program positively contributed to reducing plastic waste, enhancing students’ environmental awareness and character, fostering creativity and entrepreneurial skills, and improving the school’s image and reputation as an environmentally-oriented excellent school. Therefore, the Ecobrick innovation program has proven to be an effective strategy for developing sustainable school excellence.